PENGARUH PROMOSI DAN FASILITAS TERHADAP KEPUTUSAN MENGINAP DI OS HOTEL BATAM - RYO RAMADHAN SYAHPUTRA; HENDRI HERMAN (JURNAL ILMIAH KOHESI, 2020)
At present, business competition in the hospitality sector is very tight. hence, the hotel management must be competitive incompeting, management must carry out attractive promotions, also provide good facilities, so that it can influenceconsumers' stay decisions. The purpose of this study is to examine and analyze the effect of promotions and facilities onlodging decisions. This research was conducted at OS Hotel Batam. The sampling technique used probability samplingtechnique with accidental sampling method, and data collection techniques used survey methods through questionnaires.The sample size taken using the Slovin formula was 288 respondents from 1026 populations. data processing methodsusing multiple linear regression method with the help of SPSS (Product Solutions and Service Statistics) version 25. The testresults prove that the promotion has a significant and positive effect on the decision to stay at a significance level of 0,000<0.05, the facility has a significant and positive effect on the decision to stay at a significance value of 0,004 <0.05 and at thesame time promotions and facilities have a significant and positive effect on the decision to stay overnight with a significancevalue of 0,000 <0.05.